2019
DOI: 10.1111/ecc.12983
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-illness of metastatic gastroenteropancreatic neuroendocrine tumours in Sweden-A population-based register-linkage study

Abstract: The objective was to estimate the cost‐of‐illness of grades 1 and 2 metastatic gastroenteropancreatic neuroendocrine tumours (GEP‐NETs) in Sweden in 2013 in a population‐based study including all patients diagnosed between 2005 and 2013. Data were obtained from national registers, and patients who utilised healthcare resources due to metastatic GEP‐NETs in 2013 were included. The study included 478 patients (mean age 64 [SD=11] years, 51% men). The majority (80%) had small intestinal NET, 10% had pancreatic NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…For example, patients in the octreotide group had a higher rate of small intestine tumor and Grade 2 tumors, whereas pancreatic tumors were more common in the lanreotide group. Registry data have shown that patients with small intestinal tumors have a higher prevalence of SSA use compared with those with pancreatic tumors 14…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients in the octreotide group had a higher rate of small intestine tumor and Grade 2 tumors, whereas pancreatic tumors were more common in the lanreotide group. Registry data have shown that patients with small intestinal tumors have a higher prevalence of SSA use compared with those with pancreatic tumors 14…”
Section: Discussionmentioning
confidence: 99%
“…PanNETs are also associated with a substantial economic burden. A Swedish population-registry-based study observed an annual cost of EUR 37,000 per patient with low-grade metastatic PanNETs, similar to breast and prostate cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, RECOSY is the first study to report the use of resources and the associated direct and indirect costs for CS in Spain, and is among the few that exist for European countries [23,30]. It provides detailed data on the scope of the healthcare and economic burden of CS in this setting.…”
Section: Discussionmentioning
confidence: 99%